2007
DOI: 10.1074/jbc.m608623200
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific Conformational Studies of Prion Protein (PrP) Amyloid Fibrils Revealed Two Cooperative Folding Domains within Amyloid Structure

Abstract: Despite the ability of most proteins to form amyloid, very little is know about amyloid fibril structures and the factors that govern their stability. Using amyloid fibrils produced from fulllength prion protein (PrP), we describe a reliable approach for determining both site-specific and global conformational stability of the fibrillar form. To measure site-specific stability, we produced six variants of PrP by replacing the residues at positions 88, 98, 127, 144, 196, and 230 with cysteine, labeled the new c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
49
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 48 publications
10
49
0
Order By: Relevance
“…As suggested by the molecular dynamics simulations, the residues 184-223 have a high tendency to undergo a transition from a-helical to a bÀ or random-coil state and, therefore, might be involved in the initial stages of the conversion from PrP C to PrP Sc (Dima and Thirumalai 2004). Consistent with the simulation results, our recent kinetics studies showed that the C-terminal part encompassing residues 196-230 was involved in the early stages of polymerization (Sun et al 2007). Furthermore, in amyloid fibrils produced in vitro, residue 218 is located within the PK-resistant cross b-sheet core.…”
Section: Discussionsupporting
confidence: 78%
“…As suggested by the molecular dynamics simulations, the residues 184-223 have a high tendency to undergo a transition from a-helical to a bÀ or random-coil state and, therefore, might be involved in the initial stages of the conversion from PrP C to PrP Sc (Dima and Thirumalai 2004). Consistent with the simulation results, our recent kinetics studies showed that the C-terminal part encompassing residues 196-230 was involved in the early stages of polymerization (Sun et al 2007). Furthermore, in amyloid fibrils produced in vitro, residue 218 is located within the PK-resistant cross b-sheet core.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast to frequently discussed theoretical models (31,32), available experimental data clearly indicate that formation of rPrP amyloid involves major refolding of the native C-terminal ␣-helices to ␤-sheet structure (22,23,26,27). However, to date, recombinant PrP amyloid has only been observed to form under distinctly nonphysiological conditions, in the presence of chemical denaturants (19 -23, 25-28).…”
Section: Discussionmentioning
confidence: 93%
“…Biophysical and structural aspects of this conversion reaction remain poorly understood, largely because of fundamental difficulties of studies with brain-derived material. In recent years, however, significant advances have been made in elucidating the mechanism of conformational transitions of the recombinant prion protein (18 -21, 24, 27, 28), including structural characterization of PrP Sc -mimicking rPrP amyloid fibrils (22,23,26,27) as well as attempts to generate infectious material from purely synthetic components (25).…”
Section: Discussionmentioning
confidence: 99%
“…The physical properties of human PrP fibrils such as conformational stability appear to determine to a large extent their biological effects (48). To evaluate the conformational stability, the fibrils produced from human prion protein in the absence and presence of crowding agents were incubated in the presence of increasing concentrations of guanidine thiocyanate (from 0 to 3.5 M) for 1 h, and the amount of intact amyloid structure was analyzed using the ThT binding assay.…”
Section: Effects Of Macromolecular Crowding On Conformational Stabilimentioning
confidence: 99%